(untitled) (REMUNOM, 2026)
The arrangement of furniture, equipment, and raw materials in micro and small businesses is rarely planned in a structured way with appropriate methods that optimize workflow. Given this reality, this work used scientific methods with the aid of appropriate tools to diagnose the layout problems employed in a bakery and proposed a simple and effective restructuring to enhance the flow of the business’s production process. In turn, the study demonstrated that the adoption of re-layout methodologies, such as the spaghetti diagram and the 5W2H action plan, are efficient and fundamental in the reorganization of production spaces.